Marked oestrous cycle‐dependent regulation of rat arterial KV7.4 channels driven by GPER1. (11th October 2022) - Baldwin, Samuel N.; Forrester, Elizabeth A.; Homer, Natalie Z. M.; Andrew, Ruth; Barrese, Vincenzo; Stott, Jennifer B.; Isakson, Brant E.; Albert, Anthony P.; Greenwood, Iain A.
Abstract : Background and Purpose: Kcnq ‐encoded KV 7 channels (termed KV 7.1–5) regulate vascular smooth muscle cell (VSMC) contractility at rest and as targets of receptor‐mediated responses. However, the current data are mostly derived from males. Considering the known effects of sex, the oestrous cycle and sex hormones on vascular reactivity, here we have characterised the molecular and functional properties of KV 7 channels from renal and mesenteric arteries from female Wistar rats separated into di‐oestrus and met‐oestrus (F‐D/M) and pro‐oestrus and oestrus (F‐P/E). Experimental Approach: RT‐qPCR, immunocytochemistry, proximity ligation assay and wire myography were performed in renal and mesenteric arteries. Circulating sex hormone concentrations were determined by liquid chromatography–tandem mass spectrometry. Whole‐cell electrophysiology was undertaken on cells expressing KV 7.4 channels in association with G‐protein‐coupled oestrogen receptor 1 (GPER1). Key Results: The KV 7.2–5 activators S‐1 and ML213 and the pan‐KV 7 inhibitor linopirdine were more effective in arteries from F‐D/M compared with F‐P/E animals. In VSMCs isolated from F‐P/E rats, exploratory evidence indicates reduced membrane abundance of KV 7.4 but not KV 7.1, KV 7.5 and Kcne4 when compared with cells from F‐D/M. Plasma oestradiol was higher in F‐P/E compared with F‐D/M, and progesterone showed the converse pattern. Oestradiol/GPER1 agonist G‐1 diminished KV 7.4 encoded currents and ML213 relaxations and reduced the membrane abundance of KV 7.4 and interaction between KV 7.4 and heat shock protein 90 (HSP90), in arteries from F‐D/M but not F‐P/E. Conclusions and Implications: GPER1 signalling decreased KV 7.4 membrane abundance in conjunction with diminished interaction with HSP90, giving rise to a 'pro‐contractile state'. Abstract :